Understanding melanoma stem cells. (May 2015) - Nguyen, Nicholas; Couts, Kasey L; Luo, Yuchun; Fujita, Mayumi
SUMMARY : Tumors are incredibly diverse and contain many different subpopulations of cells. The cancer stem cell (CSC) subpopulation is responsible for many aspects of tumorigenesis and has been shown to play an important role in melanoma development, progression, drug resistance and metastasis. However, it is becoming clear that tumor cell populations are dynamic and can be influenced by many factors, such as signals from the tumor microenvironment and somatic evolution. This review will present the current understanding of CSCs and the challenges of identifying and characterizing this dynamic cell population. The known characteristics and functions of melanoma stem cells, and the potential for therapeutic targeting of these cells in melanoma, will be discussed.